A Study to Evaluate the Effectiveness of Self-Instructional Module on Knowledge Regarding Risk Factors and Prevention of Stomach Cancer among Professional Students at Selected Colleges, Bangalore - Khaling, Dipa Rai; KC, Sudikshya; Malla, Chandani (Med Phoenix, 2017)
Background: Cancer is one of the most important causes of morbidity and the magnitude of the problem is gigantic. Gastric cancer is the second leading cause of cancer mortality in the world as well as in India. Majority of the patients are diagnosed at an advanced stage. It is widely held that 80% to 90% of stomach cancers may be attributable to environmental and life style factors such as tobacco, alcohol and dietary habits. Primary cancer prevention refers to avoiding cancer causing substances in the environment or dietary elements associated with increased risk. Methods: The research approach adopted for the study was experimental approach and research design selected for the study was experimental one group pre-test post-test design. Simple random sampling technique was used for the selection of 60 professional students. The tool used for the data collection was structured knowledge questionnaire, which had two sections. Section-A provides about socio-demographic data and Section-B deals with knowledge on risk factors and prevention of stomach cancer. Collected data was analyzed by using descriptive and inferential statistics in terms of frequencies, percentage, mean, standard deviation, chi-square values and ‘t’ test. Results: The result of this study showed that in pre-test 43(71.67%) of them had inadequate level of knowledge, 17(28.33%) of them had moderate level of knowledge and none of them had adequate level of knowledge regarding risk factors and prevention of stomach cancer whereas in post-test, 40(66.67%) of them had adequate level of knowledge, 20(33.33%) of them had moderate level of knowledge and none of them had inadequate level of knowledge regarding risk factors and prevention of stomach cancer. The enhancements mean score was 16.72±1.28. Conclusion: The study was found to be effective in improving the knowledge of professional students regarding risk factors and prevention of stomach cancer. Med Phoenix Vol.2(1) July 2017, 8-11